Corrida e caminhada: orientações para uma prática saudável - Spoldaro, Diego Machado [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
In current times, technological advances, among other factors imposed by modernity, associated with the conditions experienced by humanity, direct our daily lives to a sedentary lifestyle. In a scenario of a pandemic caused by COVID-19, this perspective intensifies, as the isolation measures, the guidelines to stay at home, avoid agglomeration, lead us towards the consequences of a sedentary lifestyle, bringing to light a current scenario of stress, anxiety , depression, low conditioning, low sleep quality, exposing our body to diseases such as hypertension, obesity and diabetes, among others. As the practice of walking/running is in great demand due to its ease and benefits and mainly because of its popularization, it is necessary to search for guidelines that best serve the population, based on scientific information that allows the elaboration of a practical guide that makes the safest practice to perform. Therefore, the present study proposes to provide information on different methods and guidelines to make the practice of walking and/or running as safe as possible, favoring better use, assisting in the preparation and execution of your training sessions, serving as a guide advisor on different factors that can contribute to a better use and safety during the practice of these activities, making them healthy practices. A literature review was carried out on possible factors that interfere with performance during physical activities [food, hydration, time, temperature, clothing, footwear and exercise program variables (type, duration, intensity, frequency)] providing guidelines for development of a practical walking and running guide. For the survey, periodical publications (newspapers and magazines, printed or virtual), scientific articles, dissertations and academic monographs, published in the last 20 years, were selected. As a result, the present study brought information that contributes to the safe and efficient practice of walking and/or running, serving different audiences, whose main recommendations include: performing the practice at the time when the individual is most willing; avoid high ambient temperature, minimizing exposure to the sun; hydrate before and during practice, be well fed, ingest fast-absorbing foods, wear shoes with low soles, without heels, allowing full contact of the feet with the ground; use of comfortable clothing that allows good cooling, prior warm-up, including stretching protocols; performing the exercise within intensity ranges that are appropriate to the fitness level and the practitioner's objective.

Nos tempos atuais, avanços tecnológicos, dentre outros fatores impostos pela modernidade, associados às condições vividas pela humanidade, direcionam nosso cotidiano ao sedentarismo. Em um cenário de pandemia pela COVID-19, esta perspectiva se intensifica, pois as medidas de isolamento, as orientações para ficar em casa, evitar aglomeração, nos levam em direção às consequências do sedentarismo, trazendo à tona um cenário atual de estresse, ansiedade, depressão, baixo condicionamento, baixa na qualidade do sono, expondo nosso organismo a doenças como hipertensão, obesidade e diabetes, dentre outras. Como a prática de caminhada/corrida tem grande procura devido a sua facilidade e seus benefícios e principalmente pela sua popularização, faz-se necessário a busca por orientações que melhor atendam à população, fundamentadas em informações científicas que permitam elaborar um guia prático que tornam a prática o mais segura para ser realizada. Portanto, o presente estudo se propõe a fornecer informações sobre diferentes métodos e orientações para tornar a prática da caminhada e/ou da corrida o mais segura possível, favorecendo melhor aproveitamento, auxiliando na preparação e execução de suas sessões de treinamento, servindo como um guia orientador sobre diferentes fatores que possam contribuir para um melhor aproveitamento e segurança durante a prática destas atividades, tornando-as práticas saudáveis. Foi realizada uma revisão de literatura sobre possíveis fatores que interferem no rendimento durante a realização de atividades físicas [alimentação, hidratação, horário, temperatura, vestimenta, calçado e variáveis do programa de exercícios (tipo, duração, intensidade, frequência)] fornecendo orientações para elaboração de um guia prático de caminhada e corrida. Para o levantamento, foram selecionadas publicações periódicas (jornais e revistas, impressas ou virtuais), artigos científicos, dissertações e monografias acadêmicas, publicadas nos últimos 20 anos. Como resultado, o presente estudo trouxe informações que contribuem para a prática segura e eficiente da caminhada e/ou corrida, atendendo diversos públicos, cujas principais recomendações incluem: realização da prática no horário em que o indivíduo apresenta maior disposição; evitar temperatura ambiente elevada, minimizando a exposição ao sol; hidratar-se previamente e durante a prática, estar bem alimentado, ingerir alimentos de rápida absorção, uso de calçados com solado baixo, sem salto, permitindo contato inteiro dos pés com o solo; utilização de vestimentas confortáveis, e que permitam boa refrigeração, realização de aquecimento prévio, incluindo protocolos de alongamentos; realização do exercício dentro de faixas de intensidade que estejam adequadas ao nível de condicionamento e ao objetivo do praticante. Palavras chaves: alimentação, hidratação, horário, temperatura, vestimenta, calçado, atividade física, intensidade de treinamento.
Running and walking: guidelines for a healthy practice
Keywords: Walking; Race; Health; Caminhada; Corridas; Saúde